Predictors of referral behaviour and intention amongst physicians in a medical consortium based on the theory of planned behaviour: a cross-sectional study in China - Dongbao Zhao; Shengliang Chen; Sihui Jin; Lijin Chen; Caiyun Zheng; Xin Wang; Yixiang Huang (Frontiers Media S.A., 2023)
IntroductionTo promote patients' referral across healthcare institutions and integrated care delivery, we identified predictors of physicians' behaviour and intention to refer patients in a county medical consortium in China on the basis of the theory of planned behaviour (TPB).MethodsThis census-based cross-sectional study was conducted in Yangxi Hospital Group (YHG). All physicians in county hospitals and township health centres were invited to participate. Structural equation modelling was employed to analyse the relationships between referral intention and behaviour and other TPB variables in the group of whole participants and in sub-groups.ResultsIn total, 330 physicians participated in this study. One-third of participants were general practitioners, and half of them were from county hospitals. Referral behaviour of females (χ2 = 20.372, p < 0.001), who had lower education levels (χ2 = 17.859, p = 0.001), lower professional title (χ2 = 14.963, p = 0.005), and lower monthly salary (χ2 = 33.753, p < 0.001) were less frequent than the others. Among them, 116 (35.2%), 108 (32.7%), and 106 (32.1%) respondents reported that they had never referred patients, had referred patients 1-9 times, and had referred patients over 10 times during the past 3 months, respectively. The mean score of referral intention was 4.23/5 (SD = 0.71). In the model with all participants, a stronger referral intention (β = 0.218, 95% CI = 0.080-0.356) was associated with more frequent referral behaviour. The subjective norm (β = 0.703, 95% CI = 0.590-0.817) was the strongest predictor of physicians' referral intention, followed by perceived behavioural control (β = 0.234, 95% CI = 0.090-0.378). Mediated by referral intention, subjective norms (β = 0.153, p < 0.01) and perceived behavioural control (β = 0.190, p < 0.01) had significant indirect effects on physicians' referral behaviour. The model with participants in county hospitals showed similar results to the model with all participants. Meanwhile, in the model with participants in township health centres, there were no significant associations between referral behaviour and other TPB constructs.ConclusionPhysicians' referral behaviour was influenced by intention, subjective norms, and perceived behavioural control in Chinese county hospitals.